Semiotic analysis in Islamic-Javanese healing texts - Widyastuti, Sri Harti (Universitas Pendidikan Indonesia, 2022)
The Javanese healing texts are mostly found in Ancient Javanese and New Javanese. The texts depict the social-cultural backgrounds of the society producing the texts. Healing texts are written in particular patterns, completed with spell prayers which form the compound between the signifier and the signified. Hence, the present study is aimed at analyzing healing texts using Pierce theory and the semiotic method to find icons, indexes, and symbols. The study used the descriptive qualitative method of the Pierce approach. The data sources were texts as the transliteration result of the manuscripts Serat Primbon Djawi (Dossier of Javanese Almanac), Boekoe Primbon Djampi Jawi (Book of Javanese Medicine Almanac), Serat Primbon Jawi (Dossier of Javanese Almanac), Serat Primbon Wirid (Dossier of Spell Almanac), Serat Primbon (Dossier of Almanac) and Serat Primbon Jampi (Dossier of Almanac of Javanese Medicine) transliteration by Bratakesawa. The data were analyzed using the descriptive technique in which the data worthiness was appraised by semantic validity and intra-rater validity. Findings show that all texts are constructed of semiotic structures of icons, indexes, and symbols. In the icons, there are similar relations with verses of the Holy Quran and the nine holy clerics, spreaders of the Moslem religion. The indexes show causal relationships between the cause of the ailments and the therapies in the form of medicinal mixtures. The symbols function to show resentment of cultures that brace them and relate between icons and indexes for the unified healing formulations that are integrated and have suggestive powers.